Genetics and clinical phenotypes in common variable immunodeficiency - Cunningham-Rundles, Charlotte; Casanova, Jean-Laurent; Boisson, Bertrand (Frontiers in Genetics, 2024)
Common variable immunodeficiency (CVID) is one of the most common symptomatic groups of inborn errors of immunity. In addition to infections resulting from insufficient levels of immune globulins and antibodies, many patients develop inflammatory or autoimmune conditions, which are associated with increased mortality. This aspect of CVID has been the focus of many studies, and dissecting the clinical phenotypes of CVID, has had the goal of providing biomarkers to identify these subjects, potentially at the time of diagnosis. With the application of whole exome (WES) and whole genome analyses, an increasing number of monogenic causes of CVID have been elucidated. From the standpoint of the practicing physician, an important question is whether the clinical phenotype, particularly the occurrence of autoinflammation of autoimmunity, might suggest the likelihood of identifying a causative mutation, and if possible the gene most likely to underlie CVID. We addressed this question in a patient group of 405 subjects diagnosed with CVID from one medical center.